Genitive Case Assignment in Pashto Nested Possessor DPs and Arguments of a De-verbal Noun DPs - Talat Masood (JSSH, 2023)
The goal of this paper is to propose a mechanism for the assignment of genitive Case in Pashto nested possessor Determiner Phrases (DPs) and arguments of a de-verbal noun DPs. This study is significant in the context of the fact that of the few studies that have been carried out on the assignment of genitive Case, none has been able to explain, in an adequate way, the assignment of genitive Case in Pashto nested possessor DPs and arguments of a de-verbal noun DPs.